2021
DOI: 10.1002/anie.202111021
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Subsurface Oxygen Formation in Oxide‐Derived Cu by X‐ray Photoelectron Spectroscopy

Abstract: Subsurface oxygen has been proposed to be crucial in oxide-derived copper (OD-Cu) electrocatalysts for enhancing the binding of CO intermediates during CO 2 reduction reaction (CO 2 RR). However,t he presence of such oxygen species under reductive conditions still remains debated. In this work, the existence of subsurface oxygen is validated by grazing incident hard X-rayphotoelectron spectroscopy, where OD-Cu was prepared by reduction of Cu oxide with H 2 without exposing to air.T he results suggest two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 52 publications
3
28
2
Order By: Relevance
“…Meanwhile, another shoulder (marked by the red dashed line) shows up at the higher kinetic energy at ∼46 min and becomes a predominant peak after ∼90 min of the H 2 exposure. This peak has a kinetic energy of 918.6 eV, which corresponds to metallic Cu. ,, Along with the dominant presence of the metallic Cu peak, the time sequence of the Cu LMM spectra shows that the Cu 2 O peak (916.9 eV), together with the two intermediate peaks at 915.3 and 917.8 eV, disappears at ∼110 min, indicating that the Cu 2 O overlayer is completely reduced to metallic Cu after the extended H 2 exposure.…”
mentioning
confidence: 89%
“…Meanwhile, another shoulder (marked by the red dashed line) shows up at the higher kinetic energy at ∼46 min and becomes a predominant peak after ∼90 min of the H 2 exposure. This peak has a kinetic energy of 918.6 eV, which corresponds to metallic Cu. ,, Along with the dominant presence of the metallic Cu peak, the time sequence of the Cu LMM spectra shows that the Cu 2 O peak (916.9 eV), together with the two intermediate peaks at 915.3 and 917.8 eV, disappears at ∼110 min, indicating that the Cu 2 O overlayer is completely reduced to metallic Cu after the extended H 2 exposure.…”
mentioning
confidence: 89%
“…Even single-crystal facets of Cu, that is, Cu(111), Cu(100), and Cu(110), do not necessarily provide well-defined surface sites because CO is known to reconstruct Cu surfaces under reaction conditions. For example, a recent study showed that single-crystal surfaces were significantly roughened and reconstructed after the CO 2 RR . Multiple oxygen-containing species are present on Cu surfaces at the CO 2 RR conditions, though their roles in reactions are less clear. ,, Due to the low solubility of CO 2 and CO in aqueous electrolytes, reported activities are often impacted, if not limited, by mass transport of reactants to catalyst surfaces. , The scarcity of rigorous kinetic data has been a major barrier in the electrokinetic analysis of the CO (2) RR. We recently reported a gas-diffusion-type electrode capable of producing rigorous electrokinetic data in the CORR at a low-to-medium overpotential range. , Tafel slopes of ∼120 mV/dec were measured for all C 2+ products on a polycrystalline Cu powder, indicating that the rates were pH independent and determined by the first electron transfer during the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of low amount of residual oxygen inside an oxide-derived copper catalyst during CO 2 reduction conditions has been demonstrated by oxygen isotopic labeling (<1% of the original content within 100 nm) . Recently, an independent study has detected the presence of residual oxygen under reductive conditions through grazing incident hard X-ray photoelectron spectroscopy . The authors identified those species as oxygen present at defects and/or vacancies on the surface and oxygen intercalated within metal layers.…”
Section: Challenges From Electrocatalytic Processes Under Working Con...mentioning
confidence: 99%
“…119 Recently, an independent study has detected the presence of residual oxygen under reductive conditions through grazing incident hard X-ray photoelectron spectroscopy. 126 The authors identified those species as oxygen present at defects and/or vacancies on the surface and oxygen intercalated within metal layers. Arań-Ais et al showed that C 2+ products formation correlates with the amount of surface defects and percentage of Cu(I) site during pulsed CO 2 electroreduction.…”
Section: Reconstruction Of Active Sites During Operationmentioning
confidence: 99%